Endosalpingiosis of Axillary Lymph Nodes: A Rare Histopathologic Pitfall with Clinical Relevance for Breast Cancer Staging. (21st March 2016) - Nomani, Laila; Calhoun, Benjamin C.; Biscotti, Charles V.; Grobmyer, Stephen R.; Sturgis, Charles D.
Abstract : Establishment of accurate axillary lymph node status is of essential importance in determining both prognosis and the potential need for adjuvant therapy in patients with invasive breast cancer. Axillary lymph node heterotopias can in some cases result in overdiagnosis of metastatic disease. Nodal endosalpingiosis is perhaps the least commonly reported type of axially lymph node heterotopia. We herein illustrate a case in which second opinion pathologic interpretation combined with ancillary immunohistochemical studies allowed for a specific diagnosis of axillary nodal müllerian-type inclusions, confirming ypN0 staging and resulting in appropriate disease management and prognostication.